Novel Sorghum Herbicides for Grass Control in Fallow - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
This study was conducted to compare herbicides for use in herbicide-tolerant grain sorghum for grass control in fallow. Imazamox applied preemergence (PRE) was generally the most effective herbicide regardless of weed species or evaluation date. Postemergence (POST) treatments did not control green foxtail more than 78% late in the season. Imazamox, Assure II (quizalofop), and Accent (nicosulfuron) applied PRE or early POST controlled shattercane and crabgrass 90% or more late in the season. Assure II applied late POST also controlled shattercane 93 to 95% late in the year.
Keywords: Herbicide-resistant grain sorghum chemicals